Indonesia Tourism Recovery in Collaboration with China as a Powerful Country in Travel - I Nyoman Gede Krishna Aryawiguna (International Journal of Glocal Tourism, 2021)
Purpose: The 2019 novel coronavirus (Covid-19) outbreak is projected to have unprecedented effects on the global tourism especially to the hospitality industry. This paper aims to examine how the outbreak may alter Chinese tourists’ travel behavior, lifestyle changes and tourism preferences in the short and long term. Research methods: This paper employs qualitative research method to understand the most aspect influence towards Indonesia and China partnership in the tourism post-pandemic. It is based on the synthesis of news broadcasted by several media outlets to be supported by an overview of the related literature on online travel, tourism marketing, tourism management and tourist behavior. Findings: China have that hidden potential in the tourism sector awaiting to be awaken. Data shows that only about one-tenth of China's 1.4 billion people hold passports, a relatively small figure. It is reported that Chinese travelers spent more than 120 billion U.S. dollars overseas last year, surpassing other countries. Implication: China should be the focus for Indonesia’s tourism rebound post Covid-19. The massive volume and projected spending of travelers could support the economy of Indonesia both in short and long period of time.